Analisis Potensi Pariwisata Kuliner di Kota Bandung - Muhammad Fernanda Aria; Widiya Hidayanti (Inovasi Pendidikan dan Anak Usia Dini, 2024)
Culinary is currently known as one of the potentials of a tourist destination, culinary offerings in the form of food or snacks typical of a tourist destination are sought after by tourists who come to visit, trying local culinary delights has become an experience that tourists want to experience. The development of the tourism industry can provide opportunities for tourism products including culinary delights in the city of Bandung. The high development of the tourism industry provides enormous opportunities for the community to participate in the development of culinary tourism, which is currently still very limited in number. The aim of this article is to analyze the tourist attraction of culinary tourism in Bandung. This research uses qualitative research methods based on the results of observations and literature studies by describing the attractions of culinary tourism in Bandung. The results of this article explain traditional local culinary foods.